Fitoakumulasi Logam Berat Pb dan Cr pada Rhizophora mucronata di Sekitar Kawasan Bekas Tambang Bauksit, Pulau Bintan - Diana Azizah; Rasoel Hamidy; Mubarak Mubarak; Efriyeldi Efriyeldi (Dinamika Lingkungan Indonesia, 2021)
Bintan Island has a high potential for bauxite mining. Many ex-mining areas have not been reclaimed properly, resulting in erosion and accumulation of heavy metals Pb and Cr which are high in the sediment (red-mud) and deposited in the roots of mangrove forests on the coast of Bintan. Rhizophora mucronata is one of the species that dominates the Bintan mangrove forest. The purpose of this study was to determine the phytoaccumulation of Pb and Cr metals in R. mucronata in the former bauxite mining area ofBintan Island. This research was conducted by survey, digested and analysed using Atomic Absorption Spectrophotometer (AAS). The concentrationof Pb and Cr in the sediment, as well as the roots, stems and leaves of R. mucronata were used for the analysis of phytoaccumulation types. The results of the Pb concentration test were higher than Cr. Based on the sampling location, the concentration of Pb metal accumulation in the sediment is Tembeling <Sei Carang <Wacopek <Senggarang, while Cr metal is Tembeling <Wacopek <Sei Carang <Senggarang. The highest metals accumulation in R. mucronata was found in the roots (Pb = 3,3482 ppm, Cr = 0,7664 ppm), while the leaves (Pb = 1,1076 ppm, Cr = 0,0413 ppm) had the lowest concentration. Based on the type of accumulation, R. mucronata absorbs Pb metal with a rhizofiltration mechanism (TF <1), which means that the roots of R. mucronata effectively translocate Pb as a pollutant to its body from the soil. In addition, the bio-concentration factor (BCF) concentration of R. mucronata <1 indicates the role of R. mucronata as a plant that accumulates very little Pb (low accumulator/non-hyperaccumulator). This adaptation mechanism is important information in the rehabilitation of mangrove areas using R. mucronata, because it can still live and grow in an environment contaminated with Pb metal by absorbing a little Pb from the soil and translocating it effectively in its organs.